Epilithic diatoms (Bacillariophycae) from streams in Ramsar, Iran - Soltanpour-Gargari, Ali; Lodenius, Martin; Hinz, Friedel (Acta Botanica Croatica, 2011)
Epilithic diatoms were identified from five small streams and one canal in Ramsar, northwest Iran. Atotal of 155 diatom taxa belonging to 37 genera were found and only two species remained unidentified (Fragilaria sp. and Nitzschia sp.). Achnanthes, Nitzschia, Navicula, Cocconeis, Melosira, Amphora, Craticula, Diatoma, Surirella, Cymbella, Diploneis and Entomoneis were among the most abundant genera. Eighty seven taxa were recorded for the first time in Iran. Thirty two of the genera belong to the Pennales and 5 to the Centrales. Species richness was rather high ranging from 66 to 95Â axa at the six sites studied. The epilithic diatom species found in Ramsar were dominated by cosmopolitan taxa found in meso- to fairly eutrophic waters with high conductivity and high nutrient concentrations. The abundances found at all six sites were compiled in order to estimate the overall abundance of each taxon in Ramsar. This study includes EM pictures of diatoms observed in Ramsar, Iran.